Symptom burden in patients with cancer who are experiencing unplanned hospitalization. Issue 12 (13th March 2020) - Newcomb, Richard A.; Nipp, Ryan D.; Waldman, Lauren P.; Greer, Joseph A.; Lage, Daniel E.; Hochberg, Ephraim P.; Jackson, Vicki A.; Fuh, Charn‐Xin; Ryan, David P.; Temel, Jennifer S.; El‐Jawahri, Areej R.
Abstract : Background: Inpatient supportive care programs often target patients with advanced solid tumors. To the authors' knowledge, few studies to date have characterized symptom burden in hospitalized patients with potentially curable cancers. The objective of the current study was to compare symptom burden, palliative care consultation, and readmission rates in hospitalized patients by cancer type and treatment intent. Methods: The authors conducted a single‐center study of hospitalized patients with cancer between 2014 and 2017. They assessed physical symptoms using the Edmonton Symptom Assessment System and psychological distress using the Patient Health Questionnaire‐4 and the Primary Care PTSD (Posttraumatic Stress Disorder) Screen. Multivariate linear regression models were used to assess symptom burden, logistic regression was used to assess palliative care use, and competing risk regression was used to compare 90‐day readmission risk. Results: A total of 1549 patients were enrolled and surveyed. The majority of patients reported moderate to severe fatigue, poor well‐being, and drowsiness with no significant differences noted by cancer type and treatment intent. Compared with other groups, patients with incurable solid cancer reported higher physical symptoms (beta coefficient [B], 4.73; P  < .01) and symptoms of depression (B, 0.44; P  < .01) and anxiety (B, 0.39; P  < .01), but no difference in posttraumatic stress disorder. Among patients in the top quartile symptom burden according to the Edmonton Symptom Assessment System, the palliative care service was consulted in 14.7%, 7.9%, 25.0%, and 49.6%, respectively, of patients with potentially curable hematologic, potentially curable solid, incurable hematologic, and incurable solid cancers ( P  < .001). Compared with patients with potentially curable solid cancer, patients in each group experienced a higher risk of readmission within 90 days. Conclusions: Hospitalized patients with cancer experience substantial physical and psychological symptoms. Palliative care rarely is consulted for highly symptomatic patients with potentially curable cancers. Supportive care interventions should target the needs of symptomatic patients regardless of treatment intent. Abstract : The majority of patients with cancer with an unplanned hospitalization report substantial physical and psychological symptoms. It is interesting to note that patients with hematologic cancers and potentially curable solid cancers receive significantly fewer inpatient palliative care consultations.